The cancer-associated fibroblast facilitates YAP liquid-liquid phase separation to promote cancer cell stemness in HCC - Wei Chen; Yanling Li; Qiaodan Zhou; Wang Peng; Mengdie Cao; Yuchong Zhao; Zihan Yang; Si Xiong; Hai Huang; Luyao Liu; Shuya Bai; Bin Cheng (Cell Communication and Signaling)
Abstract Cancer stem cells (CSCs) are strongly associated with the refractory characteristics of Hepatocellular carcinoma (HCC). However, the complex interaction between CSCs and the tumor microenvironment remains incompletely understood. In this study, we identified a novel long non-coding RNA (lncRNA) NEAT1 in cancer-associated fibroblast (CAFs)-derived extracellular vesicles (EVs) that play a critical role in the induction of CSCs and HCC tumorigenesis. NEAT1 was significantly overexpressed in human HCC tissues. Furthermore, high expression of lncRNA NEAT1 in EVs was found to be associated with poor prognosis. Knockdown of NEAT1 in CAFs inhibited invasion, migration, and tumor growth. Mechanistically, NEAT1 promoted cancer cell stemness, including 3D spheroid formation, by facilitating the liquid-liquid phase separation (LLPS) of the transcription factor YAP. Specifically, NEAT1 is directly bound to the intrinsic disordered region in the YAP protein, promoting the formation of LLPS biomolecular condensates. Additionally, a positive correlation between NEAT1 and Nanog was observed in clinical HCC tissues. In conclusion, our findings reveal that NEAT1 promotes HCC carcinogenesis and CSC induction by facilitating the LLPS of the YAP protein.